Pengaruh Green Marketing Dan Green Product Terhadap Keputusan Pembelian Pupuk Organik Di Kios Tani Mulyo Kedungrejo Kabupaten Lumajang - Irawati, Reni Selvi; Nawangsih, Nawangsih (Jurnal Ilmu Manajemen Advantage, 2017)
This study aims to determine the effect of green marketing and green product depend on the decision to purchase organic fertilizer in Kios Tan Mulyo Kedungrejo Lumajang regency either partially or simultaneously. The research method used is multiple linear regression method by using hypothesis test that is t test and F test. The result of research indicate that partially for green marketing variable has no influence to purchase decision of organic fertilizer. Variable of green product there is significant influence to decision of purchasing organic fertilizer. While simultaneously there is the influence of green marketing and green product on purchasing decisions of organic fertilizer with a coefficient of determination (R square) of 0.406 was showed that 40.6% of organic fertilizer purchasing decisions can be explained by green marketing and green product, while the remaining 59,4% influenced by other variables not research in this study.